Seasonal Variation in the Reproductive Biology of Gangetic Mystus: Mystus cavasius (Hamilton-Buchanan, 1822) from the Brahmaputra River in Assam - Rajbongshi, Ankur; Phukan, Bipul; Gogoi, Rinku; Sharma, Jiten; Najnin, Asifa; Barman, Manab Jyoti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Research on the reproductive biology of fish species is crucial for evaluating their aquaculture potential. Mystus cavasiusis a commercially important and widely consumed food fish in Assam. However, a comprehensive understanding of its reproductive biology within the specific agro-climatic conditions of Assam is currently lacking. Therefore, the present study aimed to investigate the detailed reproductive biology of Mystus cavasius, focusing on sex ratio, gonadosomatic index (GSI), hepatosomatic index (HSI), condition factor (K), relative condition factor (Kn), and fecundity. The present study observed a female-biased sex ratio. Monthly analysis of the gonadosomatic index (GSI), condition factor, and mean ova diameter indicated that the reproductive period for this fish species spans from May to September, with a single peak spawning event occurring in July. A high hepatosomatic index (HSI) observed during winter (December) likely indicates a state of good nutritional condition characterized by substantial energy reserves in the liver. Conversely, a low HSI value recorded in July may suggest a period of nutritional stress, potentially indicative of starvation or reduced feeding activity. The findings indicated a significant positive linear relationship between fecundity and total length, body weight, and ovary weight. Furthermore, the relative condition factor being consistently above one in both sexes suggested that the species maintains a good physiological condition throughout the year in this region.